1, 3‐Dipolar Cycloaddition of Azomethine Ylides Involving 3‐Aminooxindoles: Versatile Construction of Dispiro[pyrrolidine‐2, 3′‐oxindole] Scaffolds. Issue 32 (26th October 2016) - Wei, Qian; Zhu, Guodong; Zhang, Hailei; Qu, Jingping; Wang, Baomin
Abstract : A three‐component [3+2] cycloaddition involving 3‐aminooxindoles, aldehydes, and methyleneindolinone derivatives for the synthesis of dispiro[pyrrolidine‐2, 3′‐oxindole] derivatives was developed. This reaction involves the use of readily available starting materials and mild reaction conditions. It displays broad functional‐group tolerance and provides the products in high yields with good to excellent diastereoselectivities. Abstract : Dispiro[pyrrolidine‐2, 3′‐oxindole]s are obtained through the three‐component [3+2] cycloaddition of 3‐aminooxindoles, aldehydes, and methyleneindolinones. This reaction involves the use of readily available starting materials and mild reaction conditions; it displays broad functional‐group tolerance and provides the products in high yields with good to excellent diastereoselectivities.